Estrutura eletrônica de aglomerados de CO2 com outras moléculas atmosféricas em fase gasosa - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
Carbon dioxide (CO2) is one of the most well-known and commonly used molecules in the scientific world as well as in human society, in general. It is present everywhere from the interstellar space to the ocean waters. It is present in plants, in human blood and also in industrial refrigerants. As a greenhouse gas, it absorbs the infrared radiation emitted by the earth which causes the increase in the atmospheric temperature. So, the study of intermolecular interactions between the molecules of CO2 with itself and other molecules is one of the most important and current research topics in molecular physics and quantum chemistry. Several experimental studies, mainly with spectroscopy of dimers and trimers of CO2 have been performed in recent decades. However, the number of theoretical works on clusters of CO2 is much lower compared to experiments. In this regard it is of great importance to have information on intermolecular interactions and spectroscopic properties of molecular systems containing CO2. With this motivation, we study intermolecular interactions with CO2 with itself as well as with water (H2O) , carbonic acid (H2CO3) and methanol (CH3OH) forming dimers, trimers and tetramers through van der Waals type intermolecular interactions using the method of Density Functional Theory (DFT) . These clusters can be represented by (CO2)n + X , where n = 1, 2, 3 and X = H2O, CH3OH, CO2 and H2CO3. Four different quantum chemical models formed by various combinations of different Gaussian basis sets and DFT functionals have been used to optimize the molecular geometries and to calculate the minimum of the potential energy surface of each homogeneous and heterogeneous CO2 cluster. The models are: B3LYP/6-311++G(d,p), B3LYP/aug-cc-pVDZ, BHandHLYP/6-311++G (d,p), BHandHLYP/aug-cc-pVDZ. The presence of intermolecular van der Waals interactions and the formation of hydrogen bonds introduce changes in structural energetics as well as in electrical and spectroscopic properties. In this work, we present a systematic analysis of the changes in the structural and energetic properties (formation of hydrogen bond, binding energies), electric properties (dipole moment, average polarizability) and spectroscopy of several clusters of CO2 in the gas phase.
Keywords: Dióxido de Carbono; Aquecimento global; Efeito Estufa; Hartree-Fock; Teoria do Funcional da Densidade; CIÊNCIAS EXATAS E DA TERRA: FÍSICA